Approaches to Addressing Stroke Health Disparities - Parry, Nicola (MD Conference Express, 2015)
This article highlights the serious global issue of stroke health disparities and discusses strategies to help reduce the problem. These include approaches focusing on health equity, health equity supplemented with targeted treatment, community-based participatory research, and involvement of other groups with an interest in reducing the disparity.